Preparation method of laser-induced patterned mirror symmetry copper electrode
Through laser-induced patterning and electroless copper plating methods, the preparation of mirror-symmetric copper electrodes of flexible sensor electrodes has been successfully realized, solving the problems of cumbersome processes and low universality in the prior art, and achieving high precision, simple processes and widespread application Electrode preparation.
Patent Information
- Application Number
- CN202411325679.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-09-23
AI Technical Summary
The prior art has cumbersome processes when preparing flexible sensor electrodes, and it is difficult to achieve double-sided synchronous patterning, which is less universal.
Using laser-induced patterning method, a semi-transparent copper film (ST-Cu) is used as the copper seed source, and the copper seeds are patterned by laser and sputtered to the upper and lower surfaces of the transparent PET substrate, combined with the electroless copper plating method (ECP) realizes the preparation of mirror-symmetric copper electrodes.
It realizes the preparation of mirror-symmetric copper electrodes with high precision, simple process, easy-to-get materials and wide universality. The copper layers on both sides are dense and firmly combined with the substrate, which is suitable for the integration of different surfaces of pressure and temperature sensing units.
Smart Images

Figure CN119392170A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a laser-induced patterned mirror-symmetrical copper electrode, and belongs to the technical field of electrode processing. Background Art
[0002] The patterning of sensor electrodes is to pattern conductive materials on a flexible substrate to form a conductor that can be bent, stretched or folded. It is the basis for manufacturing flexible electronic products. For flexible sensors, electrodes play the role of defining the size and distribution of sensing units, collecting and outputting the electrical signals of the sensing layer. Metals are the preferred materials for electrode preparation because of their excellent conductivity, good stability and low cost. Among the many conductive materials, copper metal has excellent conductivity (~58.5×10 6 S m -1 ) and ductility, is widely used in the field of electronic technology, and is also one of the preferred materials for electrode manufacturing.
[0003] Traditional metal patterning techniques are based on multi-step photolithography and vacuum sputtering, which are expensive and time-consuming. The organic solvents used in the photolithography process are not environmentally friendly and have poor compatibility with flexible substrates such as plastics or elastic materials. A low-cost alternative method is to print prefabricated metal nanoparticle inks on flexible substrates and then melt or reduce them into continuous conductive metal structures, but this method has great limitations on the choice of metal precursors, and high-temperature annealing (≥250°C) will damage the substrate. Another strategy is to combine patterning technology with a milder chemical plating method. Guo et al. used printing technology (dip pen nanolithography, inkjet printing, and screen printing) to pattern catalytic inks on flexible substrates such as PET, PDMS, and fabrics, and then used chemical plating to achieve metallization of designated areas. This method achieved patterning of a variety of metals (copper, silver, nickel, etc.) at room temperature and has a certain degree of universality. However, the use of precious metal-based catalytic inks and the complex pretreatment procedures of the plated substrates limit their large-scale application.
[0004] Laser direct writing is a maskless, vacuum-free and ultrafast patterning technology, in which a commonly used strategy is to directly etch the metal film by laser and remove the useless parts to indirectly obtain the desired pattern. In addition, its ultra-high instantaneous power can achieve the reduction of some metal precursors and directly form metal structures on various substrates. Metal salts are compounded with organic materials and treated with nanosecond pulse lasers to form catalytically active metal nanoparticles on flexible substrates, providing reactive sites for chemical plating. However, this method requires organic materials as receptors to absorb laser energy to generate local high temperatures for thermal reduction of metal salts, and organic materials are difficult to remove and will contaminate pre-plated materials. Chen et al. used a continuous wave laser to treat a series of aqueous mixtures of metal salts and semiconductor nanoparticles (reduced graphene oxide and carbon ink). The free electrons of the semiconductor nanoparticles were excited by the laser, triggering a chemical reduction process to form a semiconductor-metal composite structure. Metal films were directly patterned on different substrates without the intervention of chemical plating methods, and the areas not irradiated by the laser were easily washed away by water. Metal oxides such as CuO, Cu2O, ZnO, and NiO can also be reduced to metal elements by laser. Generally, their nanoparticles are mixed with dispersants and reducing agents to form a homogeneous ink, which is spread on a flexible substrate by spin coating, dipping, printing, etc., and a clean metal pattern is formed after laser reduction and cleaning. During the laser treatment process, the irradiated part undergoes a photothermal reaction, and a local high temperature is generated to sinter the reduced metal particles into a continuous structure. At the same time, other substances in the ink may be pyrolyzed under the action of the laser to generate reducing gases to promote the reduction of metal oxides. The bonding strength between the metal structure produced in this way and the substrate depends on the mechanical interlocking strength. Back et al. prepared a copper pattern on a glass substrate by laser reduction of CuO and successfully transferred it to a PET substrate, but this method has the risk of a weak bond between the metal and the substrate. In addition, the difficulty in dispersing metal oxide nanoparticles and the large amount of harmful gases generated by laser treatment are also its shortcomings.
[0005] Although the combination of patterning techniques such as printing and etching with electroless copper plating (ECP) has made outstanding contributions to the patterning of electrodes, the preparation process of the above methods is often very cumbersome, mainly due to the pretreatment of flexible substrates, such as decontamination, degreasing, micro-etching, pre-impregnation and activation. Laser patterning can replace these technologies by reducing metal precursors as active sites for electroless plating. However, the currently reported methods have special requirements for the selection of metal precursors, substrates to be plated and lasers, and most of them have the disadvantage of low universality and cannot achieve double-sided simultaneous patterning. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide a method for preparing a laser-induced patterned mirror-symmetric copper electrode. A semi-transparent copper film (Semi-Transparent Cu, ST-Cu) is prepared by laser as a copper seed source, and then the copper seed is patterned and sputtered onto the front and back surfaces of optically transparent PET by laser. The preparation of MS-Cu electrodes is realized by combining the ECP method to facilitate the integration of non-planar co-points of pressure and temperature sensing units. This method also has the advantages of high precision, simple process, easy availability of materials, and wide universality.
[0007] To achieve the above objectives, the technical solution of the present invention is as follows.
[0008] A method for preparing a laser-induced patterned mirror-symmetrical copper electrode, the method steps comprising:
[0009] (1) A copper foil tape is flatly pasted on two glass plates, and the copper foil tape is laser pretreated at a laser pulse frequency of 20 to 30 kHz. Then, two glass slides are placed on the surface of the pretreated copper foil tape, and then a laser treatment is performed at a laser pulse frequency of 10 to 20 kHz to sputter copper microparticles onto the glass slides to obtain glass slides with a semi-transparent copper film deposited thereon;
[0010] (2) placing an optically transparent substrate flatly between two glass slides deposited with a semi-transparent copper film, and then performing laser scanning on the surface of the glass slide deposited with the semi-transparent copper film located on the upper layer according to the desired electrode pattern at a laser pulse frequency of 50 to 60 kHz, so that the copper particles on the two glass slides are simultaneously sputtered to the upper and lower surfaces of the substrate, thereby obtaining a substrate having a mirror-symmetrical patterned copper seed layer;
[0011] (3) The substrate having the mirror-symmetrical patterned copper seed layer is placed in a copper plating solution at 80-90° C. for 3-5 minutes and then taken out to obtain a laser-induced patterned mirror-symmetrical copper electrode.
[0012] Preferably, in step (1), the light transmittance of the glass slide deposited with the translucent copper film is 45% to 60%.
[0013] Preferably, in step (2), the optically transparent substrate is polyethylene terephthalate (PET), polyimide (PI) or transparent glass.
[0014] Preferably, in step (2), the laser pulse frequency is 50 to 55 kHz.
[0015] Preferably, in step (2), during laser scanning, the light transmittance of the glass slide on the upper layer with the translucent copper film deposited thereon is greater than that of the glass slide on the lower layer with the translucent copper film deposited thereon.
[0016] Preferably, in steps (1) and (2), during laser pretreatment, laser treatment and laser scanning, the processing speed is 700-900 mm / s, the processing distance is 26-27 cm, the pulse width is 10-15 ns, and the scanning line spacing is 10-20 μm.
[0017] Preferably, in step (3), the copper plating solution consists of solution A and solution B; the volume ratio of solution A to solution B is 10 to 20:1;
[0018] Liquid A includes copper sulfate pentahydrate, potassium sodium tartrate tetrahydrate, hydroxide, methanol, sodium dodecyl sulfate, anhydrous potassium ferrocyanide and ammonium chloride; Liquid B is a formaldehyde aqueous solution.
[0019] Preferably, in the liquid A, the concentration of copper sulfate pentahydrate is 40-50 g / L, the concentration of potassium sodium tartrate tetrahydrate is 60-70 g / L, the concentration of the complexing agent is 60-70 g / L, the concentration of the hydroxide is 15-20 g / L, the concentration of methanol is 50-70 mL / L, the concentration of sodium dodecyl sulfate is 0.02-0.05 g / L, the concentration of anhydrous potassium ferrocyanide is 0.08-0.1 g / L, and the concentration of ammonium chloride is 0.5-1 g / L; in the liquid B, the concentration of the formaldehyde aqueous solution is 37 wt%-40 wt%.
[0020] Preferably, the hydroxide is potassium hydroxide or sodium hydroxide.
[0021] A laser-induced patterned mirror-symmetrical copper electrode is prepared by the above method.
[0022] Beneficial Effects
[0023] The present invention provides a method for preparing a laser-induced patterned mirror-symmetrical copper electrode. Through laser processing under specific conditions and combined with the ECP process, the patterning of the mirror-symmetrical copper electrode on a transparent substrate is successfully achieved. In the obtained symmetrical copper electrode, the copper layers on both sides are dense and firmly bonded to the substrate; the resistance is less affected by bending and temperature, and has excellent conductivity, and can be used as a sensor electrode.
[0024] The invention provides a preparation method of a laser-induced patterned mirror-symmetrical copper electrode. First, a copper foil tape is pasted on a glass plate, and laser pretreatment is performed to remove surface impurities, and copper is longitudinally etched at the same time, so as to generate a certain gap between a glass slide and copper to prevent the two from being welded together by molten copper particles in subsequent laser treatment; then two glass slides are respectively placed on the surfaces of the pretreated copper foil tape, and tiny copper microparticles are sputtered onto the glass slides by laser; then an optically transparent substrate is placed between the two glass slides, and a desired pattern is scanned by laser, and copper particles are simultaneously sputtered to the upper and lower surfaces of the substrate, which serve as a seed layer (catalytic active site) for chemical plating; finally, the substrate is placed in a copper plating solution for treatment to obtain a mirror-symmetrical copper electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The present invention is a preparation flow chart of the method.
[0026] Figure 2 The transmittance and SEM results of different ST-Cu in the examples and comparative examples.
[0027] Figure 3 The figures are actual images of substrates with mirror-symmetrical patterned copper seed layers at different laser frequencies in the embodiments and comparative examples.
[0028] Figure 4 The SEM image of the PET substrate with the mirror-symmetrical patterned copper seed layer obtained in Examples 1-3.
[0029] Figure 5 1 is the XPS graph of ST-Cu and the substrate PET with a mirror-symmetrical patterned copper seed layer in Example 1.
[0030] Figure 6 The SEM and AFM images of the pattern of MS-Cu and the upper and lower copper layers in Example 1.
[0031] Figure 7 The mechanical strength test results of copper in MS-Cu in Example 1. DETAILED DESCRIPTION
[0032] The present invention will be further described in detail below in conjunction with specific embodiments.
[0033] In the following examples and comparative examples, the reagents, materials and instruments used are as follows:
[0034] Copper tape (0.15 mm), glass slide (1 mm), glass plate, PET (12.5 μm), and conductive double-sided tape (10 μm, vertical resistance ≤ 0.03 Ω) are all commercial products. The chemical copper plating solution is composed of A solution and B solution. The specific parameters are shown in Table 1. When used, the ratio of A:B = 16:1 (v / v) is mixed. Under the action of the catalyst, the copper plating reaction occurs: Cu 2+ Complex + 2HCHO + 4OH - →Cu+2HCOO - +H2+2H2O+complex.
[0035] Table 1
[0036]
[0037] The laser processing system consists of a UV pulse laser (Advanced Opto-wave AMT-355-5W), a high-precision galvanometer, a computer system for controlling the pattern, and a Z-axis motor for controlling the processing distance. The focal length is 26.2 mm. The processing parameters are shown in Table 2.
[0038] Table 2
[0039]
[0040] Scanning electron microscope (SEM), atomic force microscope (AFM), and optical microscope are used to characterize the surface morphology of the material, X-ray photoelectron spectrometer (XPS) is used to characterize the element composition of the copper seed layer, force-controlled folding platform push rod (RM-RPLA-11-5-2-HP50-001) is used to test the mechanical strength of the copper film, and four-probe tester is used to measure the square resistance of the coating. Keithley 2400A is used to provide power and collect resistance signals.
[0041] like Figure 1 As shown, a method for preparing a laser-induced patterned mirror-symmetrical copper electrode comprises the following steps:
[0042] (1) Using laser to sputter a layer of translucent copper film on a glass slide: Copper foil tape is flatly pasted on two glass plates, and the copper foil tape is laser pre-treated at a laser pulse frequency of 20 to 30 kHz. Then, two glass slides are placed on the surface of the pre-treated copper foil tape, and then laser treatment is performed at a laser pulse frequency of 10 to 20 kHz to sputter copper microparticles onto the glass slide to obtain a glass slide with a translucent copper film deposited thereon. In this process, the metallic copper on the surface is melted into tiny copper particles after absorbing the energy of the laser, and an explosion occurs to sputter the molten particles onto the glass slide to form ST-Cu.
[0043] (2) placing an optically transparent substrate flatly between two glass slides deposited with a semi-transparent copper film, and then performing laser scanning on the surface of the glass slide deposited with the semi-transparent copper film located on the upper layer according to the desired electrode pattern at a laser pulse frequency of 50 to 60 kHz, so that the copper particles on the two glass slides are simultaneously sputtered to the upper and lower surfaces of the substrate, thereby obtaining a substrate having a mirror-symmetrical patterned copper seed layer;
[0044] (3) The substrate having the mirror-symmetrical patterned copper seed layer is placed in a copper plating solution at 80-90° C. for 3-5 minutes and then taken out to obtain a laser-induced patterned mirror-symmetrical copper electrode.
[0045] Example 1
[0046] (1) Copper foil tape was flatly pasted on two glass plates, and the copper foil tape was laser pretreated at a laser pulse frequency of 20 kHz. Then, two glass slides were placed on the surface of the pretreated copper foil tape, and then one of them was laser treated at a laser pulse frequency of 10 kHz to obtain a first glass slide (denoted as ST-Cu-10) with a semi-transparent copper film deposited thereon; and one of them was laser treated at a laser pulse frequency of 20 kHz to obtain a second glass slide (denoted as ST-Cu-20) with a semi-transparent copper film deposited thereon.
[0047] (2) An optically transparent substrate is placed flatly between a first glass slide and a second glass slide, and then the surface of the first glass slide is laser scanned according to the desired electrode pattern at a laser pulse frequency of 50 kHz. The copper particles on the two glass slides are simultaneously sputtered to the upper and lower surfaces of the substrate, thereby obtaining a substrate with a mirror-symmetrical patterned copper seed layer.
[0048] (3) The substrate having the mirror-symmetrical patterned copper seed layer is placed in a copper plating solution at 80° C. for 3 minutes and then taken out, and the burrs of overplating at the edge of the copper film are ultrasonically removed to make the pattern outline clear, and the substrate is rinsed with deionized water to remove the water on the surface, thereby obtaining a laser-induced patterned mirror-symmetrical copper electrode (denoted as MS-Cu).
[0049] Example 2
[0050] In step (2) of this embodiment, the laser pulse frequency is 55 kHz, and the rest is the same as in embodiment 1.
[0051] Example 3
[0052] In step (1) of this embodiment, when two glass slides are laser treated, the laser pulse frequency is 10 kHz, and in step (2) the laser pulse frequency is 60 kHz. The rest is the same as in embodiment 1.
[0053] Comparative Example 1
[0054] In step (1) of this comparative example, when two glass slides are laser treated, the laser pulse frequencies are 30 kHz (denoted as ST-Cu-30) and 40 kHz (denoted as ST-Cu-40), respectively, and the rest are the same as in Example 1.
[0055] Comparative Example 3
[0056] In this comparative example, the laser pulse frequency in step (2) is 65 kHz, and the rest is the same as in Example 1.
[0057] In the examples and comparative examples, the transmittance and SEM results of different ST-Cu are as follows: Figure 2 As shown, the results show that the transmittance of ST-Cu increases from 45.2% to 80% with the increase of laser frequency (the wavelength of the incident light is consistent with the laser wavelength, which is 355nm). The SEM test results of ST-Cu processed with different laser frequencies and the glass slide without copper particles show that there are a large number of irregularly shaped copper particles on the surface of ST-Cu, and their content decreases with the increase of frequency.
[0058] In the embodiments and comparative examples, the substrate with mirror-symmetrical patterned copper seed layer under different laser frequencies is as follows: Figure 3 As shown, the results indicate that the lower the frequency, the more favorable it is for the formation of the coating. This is because the greater the laser power, the more copper seed microparticles are sputtered and transferred.
[0059] The SEM test results of the substrate PET with mirror-symmetrical patterned copper seed layer obtained in Examples 1-3 are as follows: Figure 4As shown, a and b are schematic diagrams of the structure of the substrate with a mirror-symmetrical patterned copper seed layer, and c is the SEM result of the upper and lower surfaces of the substrate PET obtained in step (2). The results show that during the laser scanning process, the laser passes through ST-Cu and PET, sputters the copper seeds to the upper and lower surfaces of PET, and the copper microparticles that are melted again will thermally corrode PET, which is conducive to the growth and adhesion of copper during the ECP process. This step of treatment realizes micro-etching, sensitization, and patterning on both sides of the substrate, greatly simplifying the process flow and shortening the time. The SEM results of the upper and lower surfaces of PET after laser treatment with frequencies of 50, 55, and 60kHz show that micro-etching increases with the decrease of laser frequency, and there are more micron-sized copper particles on the upper surface of PET, and the micro-etching is more significant than that on its lower surface. This is because larger particles are difficult to sputter from bottom to top, and the energy of the laser is attenuated after passing through PET and ST-Cu-20. d and e are the SEM results of the upper and lower surfaces of the substrate PET obtained in step (2) of Example 1. The copper particles on the ST-Cu are irregular, while the copper particles on the PET are spherical and smaller in size. This indicates that the secondary laser treatment causes the copper particles on the ST-Cu to melt, explode, and sputter again. This process further reduces the size of the copper particles and increases their specific surface area, which may also increase their chemical reactivity and accelerate the occurrence of the copper plating reaction.
[0060] Example 1 The XPS results of ST-Cu and the substrate PET with mirror-symmetrical patterned copper seed layer are as follows: Figure 5 As shown in the figure, ST-Cu and PET both have obvious satellite peaks near 943eV, and ST-Cu is stronger, which indicates that the copper microparticles on the surface of both contain a certain amount of divalent copper, and the content of ST-Cu is higher. The two peaks other than the satellite peak were fitted, and the peaks near 935eV and 954eV correspond to the 2P 3 / 2 and 2P 1 / 2 The peaks at 933eV and 952eV correspond to the 2P peaks of zero-valent copper. 3 / 2 and 2P 1 / 2 The peak area results show that the contents of zero-valent copper in ST-Cu and PET are 46% and 76%, respectively, which indicates that during the preparation of ST-Cu, the laser will oxidize copper under the action of O2 in the air, and the oxidized copper will be reduced to a certain extent during the secondary laser sputtering to PET.
[0061] The SEM and AFM results of the pattern of MS-Cu and the upper and lower copper layers in Example 1 are as follows: Figure 6As shown, the SEM results show that the copper coating is dense, and the upper surface is rougher than the lower surface, which is caused by more significant micro-etching. The AFM results show that the surface morphology is consistent with the SEM results, and the thickness of the copper layer on the upper and lower surfaces is 600-800 and 400-500nm, respectively. The rough side can be used to make temperature sensors because it can provide more anchor points to enhance the bonding strength between GO and the electrode. In addition, the four-probe tester shows that both the upper and lower surfaces have very low square resistance, which are ~0.138±0.008 and 0.278±0.026Ω / sq, respectively.
[0062] To measure the mechanical strength of the copper coating in Example 1, a 60×2 mm long electrode was prepared, folded in a "Z" shape, fixed between two glass slides, and a force of 50 N was repeatedly applied using a force-controlled folding platform push rod. The resistance response was as follows: Figure 7 As shown in a (using conductive double-sided tape and copper foil to connect to the test instrument): the resistance increases slightly under load conditions, and decreases when the load is removed. After 63 cycles, the resistance increases sharply to several thousand ohms due to the breakage of the copper layer, and then returns to a few ohms after unfolding. This shows that the copper coating is firmly bonded to the PET substrate. In addition, the coating can withstand several tape sticking-separation tests, such as Figure 7 As shown in Figure b, no obvious coating shedding was observed after three tests, which also proves that the coating is firmly attached to PET. Figure 7 The method shown in the small illustration in c is conformally bent and fixed on cylinders of different radii, and the relationship between its resistance and bending curvature is measured (the number of samples is 3), as shown in Figure 7 As shown in c, the results show that even with a bending curvature of 0.5 mm, the resistance change of the copper electrodes on both sides is very low (ΔR<0.4Ω). Figure 7 Figure d) shows that in the range of 20-100°C, the temperature has little effect on the total resistance of the connection between the copper electrode and the conductive double-sided tape, which is less than 1Ω. It can be seen that bending and temperature have little effect on the resistance of the copper electrode and its connection, which is much lower than the resistance change caused by the pressure or temperature sensor under the same stimulus, and can therefore be ignored.
[0063] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. A method for preparing a laser-induced patterned mirror-symmetrical copper electrode, characterized in that: The method steps include: (1) A copper foil tape is flatly pasted on two glass plates, and the copper foil tape is laser pretreated at a laser pulse frequency of 20 to 30 kHz. Then, two glass slides are placed on the surface of the pretreated copper foil tape, and then a laser treatment is performed at a laser pulse frequency of 10 to 20 kHz to sputter copper microparticles onto the glass slides to obtain glass slides with a semi-transparent copper film deposited thereon; (2) placing an optically transparent substrate flatly between two glass slides deposited with a semi-transparent copper film, and then performing laser scanning on the surface of the glass slide deposited with the semi-transparent copper film located on the upper layer according to the desired electrode pattern at a laser pulse frequency of 50 to 60 kHz, so that the copper particles on the two glass slides are simultaneously sputtered to the upper and lower surfaces of the substrate, thereby obtaining a substrate having a mirror-symmetrical patterned copper seed layer; (3) The substrate having the mirror-symmetrical patterned copper seed layer is placed in a copper plating solution at 80-90° C. for 3-5 minutes and then taken out to obtain a laser-induced patterned mirror-symmetrical copper electrode.
2. The method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 1, characterized in that: In step (1), the light transmittance of the glass slide deposited with the translucent copper film is 45% to 60%.
3. The method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 1, characterized in that: In step (2), the optically transparent substrate is polyethylene terephthalate, polyimide or transparent glass.
4. The method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 1, characterized in that: In step (2), the laser pulse frequency is 50 to 55 kHz.
5. The method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 1, characterized in that: In step (2), during laser scanning, the light transmittance of the glass slide on the upper layer with the translucent copper film deposited thereon is greater than that of the glass slide on the lower layer with the translucent copper film deposited thereon.
6. The method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 1, characterized in that: In steps (1) and (2), during laser pretreatment, laser treatment and laser scanning, the processing speed is 700-900 mm / s, the processing distance is 26-27 cm, the pulse width is 10-15 ns, and the scanning line spacing is 10-20 μm.
7. The method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 1, characterized in that: In step (3), the copper plating solution is composed of solution A and solution B; the volume ratio of solution A to solution B is 10 to 20:1; Liquid A includes copper sulfate pentahydrate, potassium sodium tartrate tetrahydrate, hydroxide, methanol, sodium dodecyl sulfate, anhydrous potassium ferrocyanide and ammonium chloride; Liquid B is a formaldehyde aqueous solution.
8. The method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 7, characterized in that: In the liquid A, the concentration of copper sulfate pentahydrate is 40-50 g / L, the concentration of potassium sodium tartrate tetrahydrate is 60-70 g / L, the concentration of the complexing agent is 60-70 g / L, the concentration of the hydroxide is 15-20 g / L, the concentration of methanol is 50-70 mL / L, the concentration of sodium dodecyl sulfate is 0.02-0.05 g / L, the concentration of anhydrous potassium ferrocyanide is 0.08-0.1 g / L, and the concentration of ammonium chloride is 0.5-1 g / L; in the liquid B, the concentration of the formaldehyde aqueous solution is 37 wt%-40 wt%.
9. A method for preparing a laser-induced patterned mirror-symmetrical copper electrode according to claim 8, characterized in that: The hydroxide is potassium hydroxide or sodium hydroxide.
10. A laser-induced patterned mirror-symmetrical copper electrode, characterized in that: It is prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Laser induced graphene hybrid materials for electronic devices
CA2968886A1
Preparation method of on-chip high-quality factor chalcogenide photonic crystal plate
CN117568746A
Manufacturing method of patterned vapor deposition film
JP2008174783A
Chip resistor
JP2011199188A
Mirror symmetry microcavity and mirror symmetry microcavity laser device for generating exceptional point and method for manufacturing microcavity
KR102432685B1